Peluang Dan Tantangan Uang Digital Dalam Pembelajaran IPS Di Sekolah Dasar: Menyongsong Era Digital - Khasanah, Rohmah (Pena Edukasia, 2024)
This research is motivated by the development of money in the world which now exists in digital form. The concept of money is one of the social studies teaching materials in elementary schools. Studying the Concept of Money aims to study the development of money used in everyday life, the challenges faced, and opportunities for economic growth in the future. Students need to study material about the concept of money to deepen their understanding and develop characters related to financial intelligence, independence, creativity, skills and critical thinking. This writing aims to find out the importance of understanding the opportunities and challenges of digital money in social studies learning for Phase B Class IV students at SD Negeri Palebon 02 Semarang City with material about getting to know the function of money and the use of money in everyday life. This writing uses literature review. Data was obtained from writing findings contained in literature reviews. Data analysis involves collecting, presenting, and drawing conclusions from data. The results of this paper show that social studies learning plays an important role in introducing the concept of digital money to students through the TPACK (Technological Pedagogical Content Knowledge) approach. This concept helps teachers effectively incorporate technology into learning by understanding subject matter (content knowledge), effective learning strategies (pedagogical knowledge), and appropriate use of technology (technical knowledge). By combining these three aspects, teachers can create interesting and effective learning experiences for students